Overexpression of Lifeact in the C. elegans body wall muscle causes sarcomere disorganization and embryonic or larval lethality - Ono, Shoichiro (Frontiers in Cell and Developmental Biology, 2024)
Lifeact is a short peptide that is widely utilized as a probe for actin filaments in live imaging. However, high concentrations of Lifeact can alter actin filament dynamics and cause artificial modifications to the actin cytoskeleton. Here, I evaluated Caenorhabditis elegans strains expressing Lifeact fused to fluorescent proteins in the body wall muscle. I found that, while low-level expression of Lifeact from a single-copy transgene was appropriate for labeling sarcomeric actin filaments, overexpression of Lifeact from an extrachromosomal array causes severe disorganization of muscle sarcomeres and lethality at an embryonic or larval stage. Therefore, for imaging studies in C. elegans, Lifeact needs to be kept at a low level by proper management of the expression system.